Descriptive grammar of Middle Assyrian / Jacob Jan de Ridder. - Ridder, Jacob Jan de, 1986- (Leipziger altorientalistische Studien, 2018)
The Middle Assyrian period (ca. 1500-1000 BCE) is characterized by the transformation of the former city state of Ashur into an expansive empire. Over the last couple of decennia, the text corpus has grown considerably due to many archaeological excavations of archives in Syria. This grammatical description of Middle Assyrian seeks to improve our knowledge of the language of these texts. It takes into account recently published texts, including the archives from Tell As-SeH Hamad, Tell Huwira, Tell Sabi Abyad and Tell Taban. The result serves as a long overdue supplementation to Mayer's Untersuchungen zur Grammatik des Mittelassyrischen (1971). The monograph consists of an introduction to the corpus and its historical context, followed by discussions on orthography, phonology, morphology and syntax. Non-Assyrian influences on orthography and grammar are also subject of discussion. In addition, comparisons are made between the different stages of the Assyrian language in order to put Middle Assyrian into context of its intermediate stage between Old Assyrian (ca. 1900-1700) and Neo-Assyrian (ca. 1000-600). Thus, the monograph is aimed at Assyriologists as well as Semitists.